Profile of patients with portopulmonary hypertension - M. K. Barkovskaya; V. V. Kushnir; Z. S. Valieva; T. V. Martynyuk (Евразийский Кардиологический Журнал)
Aim. Review of clinical, functional and hemodynamic status of patients with portopulmonary hypertension Materials and methods. Clinical cases of 40 patients with portopulmonary hypertension, who hospitalized in the department of pulmonary hypertension and heart diseases of the National Medical Research Centre of cardiology named after academician E.I. Chazov of Ministry of Health in the period from 2015 to 2024 years. We have analyzed clinical, functional, hemodynamic parameters. Results. 40% of patients were men, mean age 52.6±9.7 years. More often Reasons of portopulmonary hypertension of our patients were congenital portocaval shunts, virus or toxic cirros. The time from the diagnosis of portal hypertension to the start of PAH symptoms was 3±2.8 years. Median level NT-proBNP was 526.60 pkg/mL, D-dimer 0.44.35% and 55% of these patients belonged to the high and intermediate risk groups, respectively. The mean distance in the six minute walk test was 406.8±109.2m, functional class II. Conclusion. The occurrence of portal hypertension can be caused by various reasons. This diagnosis is more often found in middle-aged women. Further dynamic monitoring of these patients will improve their clinical status and   determine their prognosis.